ANGGARAN DALAM PERSPEKTIF AGENCY THEORY - Ardini, Lilis (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2022)
The purpose of this research is to interprate the meaning of budgeting in one of State Own Enterprises in order to minimize the conflict between principal and agent. This is qualitative research and conduct through simbolic interactionism perspective in interpretive paradigm. The result of this research exposes that budgeting process involve interaction between principal and agent based on their experiences. Especially in condition where an individu can get a freedom from critical condition wich called as ephiphany. Social reality shows that the ownership of capitalist company, always thinking them selves from their self interest. As the result, the implementation of budgeting process which consist of symbols and numbers eventually will be bounded by greed. With explanation and seeking the meaning of the agency theory, capitalism of the ownership of the company offered the capitalist values in accounting information. Finally, every decision and economic behaviour will be based on capitalist values by it self.